PENYULUHAN BAHAYA ROKOK ELEKTRIK DAN PENYALAHGUNAAN OBAT PADA ANAK USIA REMAJA DI LINGKUNGAN SEKOLAH MENENGAH PERTAMA NEGERI 9 KENDARI - Ruslin Ruslin; Nita Trinovitasari; Adnan Haerun; Efi Triolni; Julfitar Julfitar; Rahmi Nurul Insani; Wd. Nurmila (MAJU : Indonesian Journal of Community Empowerment, 2026)
Smoking behavior, particularly the use of electronic cigarettes (vapes), and drug abuse among adolescents have become increasingly concerning public health issues that may adversely affect physical, mental, and social well-being. Limited knowledge regarding the dangers of electronic cigarettes and drug abuse is one of the factors contributing to these risky behaviors. This community service program aimed to improve the knowledge and awareness of students at SMP Negeri 9 Kendari regarding the dangers of electronic cigarette use and drug abuse from an early age. The program was conducted using interactive educational lectures, distribution of educational leaflets, group discussions, and question-and-answer sessions. The educational materials covered the health risks of electronic cigarettes, drug abuse, harmful chemical substances, risk factors, health consequences, and preventive measures. The results demonstrated that the students enthusiastically participated in the program, actively engaged in discussions, and showed a good understanding of the educational materials presented. The improvement in participants' knowledge was reflected in their ability to answer questions correctly and their strong interest in the topics discussed. This activity contributed positively to increasing students' awareness of the importance of avoiding electronic cigarette use and drug abuse as part of promoting a healthy lifestyle. Therefore, continuous health education through collaboration between educational institutions and healthcare professionals is essential to support the development of a healthy, productive, and drug-free younger generation.